An evaluation of perceptions of MBBS fourth professional year students on objective structured clinical examination (OSCE) in the subject of General Surgery - Nishikant N. Gujar; Vishal Jadhav; Jilani S. Awati; Sajid Ahmad Mudhol; Md Azmathulla H; Pradeep Gajakosh; Abu Talha; Tausif Alam (Al Ameen Journal of Medical Sciences)
Introduction: The Competency-Based Medical Education (CBME) curriculum, implemented in August 2019, emphasizes a comprehensive approach to learning, integrating cognitive, affective, and psychomotor domains. To address the limitations of traditional assessment methods, the Objective Structured Clinical Examination (OSCE) was introduced to reduce the bias. OSCE is now widely adopted as a gold standard for evaluating clinical skills due to its structured, objective approach and ability to minimize bias. Objectives: This study aimed to evaluate the perceptions of MBBS fourth-year students regarding the OSCE in General Surgery at Al-Ameen Medical College. Materials and Methods: Conducted over six months, this cross-sectional study involved 144 out of 149 MBBS fourth-year students who participated in an OSCE consisting of six stations: two history-taking, two clinical examination, one with a simulated patient, one with a mannequin, one skill station, and one communication station. Students completed a questionnaire via Google Forms following the OSCE. Responses were recorded on a 5-point Likert scale and analysed using Microsoft Excel, with quantitative data expressed as means and standard deviations, and qualitative data as frequencies and percentages. Statistical significance was assessed using t-tests, with p<0.05 considered significant. Results: The majority of students found the OSCE to be a practical and effective assessment tool. Key findings include that 67.62% of students felt the time for each station was adequate, 69.49% believed the OSCE identified clinical skill deficiencies, and 57.27% found the OSCE stressful. Although most students appreciated the OSCE’s relevance and objectivity, concerns about time pressure and stress were notable. Conclusion: The OSCE was generally perceived as an effective method for evaluating clinical skills and knowledge. However, students expressed concerns about the associated stress and time management challenges.